Pengaruh Mentoring Dosen Pembimbing Akademik terhadap Prestasi Akademik Mahasiswa STKIP Pembangunan Indonesia - Harti Oktarina; Sitti Hajar Aswad (Phinisi Integration Review, 2020)
This study aims to: (1) find out how the implementation of academic guidance for students of the 2016 STKIP Pembangunan Indonesia Economic Education study program, (2) find out how the academic achievements of the STKIP 2016 Indonesian Economic Education Study Program, (3) find out how the influence of academic guidance to the improvement of academic achievement of students of the 2016 STKIP Pembangunan Indonesia economic education study program. in this study were 17 students of the 2016 economic education study program. Data collection techniques using a questionnaire. Data analysis techniques using simple linear regression analysis with the help of the SPSS program. The results showed that the Mentoring of academic supervisors in the 2016 class of economic education study program was included in the qualification sufficiently in its effect on improving academic achievement. Student academic achievements in the 2016 economic education study program included in the medium qualification. This can be seen in the average results of student learning achievement is 3.66 located at intervals of 3.51 - 4.00 and including Cum Laude qualification level. There is an influence between the mentoring lecturers of academic advisers on the academic achievements of students of the 2016 Economic Education Study Program STKIP Pembangunan Indonesia. This is indicated by the value of sig. 0.007 <0.05 then Ha is accepted and Ho is rejected